Fluoroethylene Carbonate Additives to Render Uniform Li Deposits in Lithium Metal Batteries - Zhang, Xue‐Qiang; Cheng, Xin‐Bing; Chen, Xiang; Yan, Chong; Zhang, Qiang (Advanced functional materials, 2017)
Lithium (Li) metal has been considered as an important substitute for the graphite anode to further boost the energy density of Li‐ion batteries. However, Li dendrite growth during Li plating/stripping causes safety concern and poor lifespan of Li metal batteries (LMB). Herein, fluoroethylene carbonate (FEC) additives are used to form a LiF‐rich solid electrolyte interphase (SEI). The FEC‐induced SEI layer is compact and stable, and thus beneficial to obtain a uniform morphology of Li deposits. This uniform and dendrite‐free morphology renders a significantly improved Coulombic efficiency of 98% within 100 cycles in a Li | Cu half‐cell. When the FEC‐protected Li metal anode matches a high‐loading LiNi0.5Co0.2Mn0.3O2 (NMC) cathode (12 mg cm−2), a high initial capacity of 154 mAh g−1 (1.9 mAh cm−2) at 180.0 mA g−1 is obtained. This LMB with conversion‐type Li metal anode and intercalation‐type NMC cathode affords an emerging energy storage system to probe the energy chemistry of Li metal protection and demonstrates the material engineering of batteries with very high energy density. Fluoroethylene carbonate (FEC) additive is used to form a LiF‐rich solid electrolyte interphase (SEI). The FEC‐induced SEI layer is compact and stable, and therefore beneficial to obtain a uniform morphology of Li deposits. When the FEC‐protected Li metal anode matches a high‐loading oxide cathode, a high initial capacity and stable cycling are achieved.